2018
DOI: 10.1590/0074-02760170377
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dog collars impregnated with 4% deltamethrin in controlling visceral leishmaniasis in Lutzomyia longipalpis (Diptera: Psychodidade: Phlebotominae) populations

Abstract: BACKGROUND There is little information on the effect of using deltamethrin-impregnated dog collars for the control of canine visceral leishmaniasis.OBJECTIVES The objective of this study was to evaluate the effectiveness of the use of 4% deltamethrin-impregnated collars (Scalibor®) in controlling visceral leishmaniasis in Lutzomyia longipalpis by comparing populations in intervention and non-intervention areas.METHODS Phlebotomine flies were captured over 30 months in four neighbourhoods with intense visceral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 25 publications
0
19
0
4
Order By: Relevance
“…The use of insecticide-impregnated collars has been recommended as the most effective measure among those cited above [43,[53][54][55]. Silva et al [56] demonstrated a reduction of 15% (p = 0.004) in Montes Claros, MG, Brazil, and 60% (p <0.001) in Fortaleza, CE, Brazil, in the vector population of captured.…”
Section: Discussionmentioning
confidence: 99%
“…The use of insecticide-impregnated collars has been recommended as the most effective measure among those cited above [43,[53][54][55]. Silva et al [56] demonstrated a reduction of 15% (p = 0.004) in Montes Claros, MG, Brazil, and 60% (p <0.001) in Fortaleza, CE, Brazil, in the vector population of captured.…”
Section: Discussionmentioning
confidence: 99%
“…The use of insecticide-impregnated collars has been recommended as the most effective measure among those cited above [37,[47][48][49]. Silva et al [50] demonstrated a reduction of 15% (p = 0.004) in Montes Claros, MG, Brazil, and 60% (p <0.001) in Fortaleza, CE, Brazil, in the vector population of captured. Kazimoto et al [51] observed that there was a 53-59% reduction in the VL incidence in dogs resulting from the use of these collars.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the collars must be changed every six months and replaced when lost. As a result, the authors warn of their high cost when used on a large scale [50,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The recommended VL control options in Brazil include the reactive application of insecticides in houses and animal sheds to reduce vector numbers, the euthanasia of seropositive domestic dogs, the diagnosis and treatment of human cases, and public education [ 15 , 16 ]. However, despite the efforts of the Ministry of Health, the burden (calculated from the mortality, morbidity, and disability) of VL in Brazil more than doubled between 1990 and 2016 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%